Sosialisasi Storytelling Melalui Media Gambar Pada Anak Usia Dini - Nissa, Khairun; Putri, Jihan Hidayah (Jurnal Pengabdian Masyarakat Inovasi, 2025)
Literacy and speaking skills in early childhood are the primary foundations for their cognitive and socio-emotional development. However, challenges in the field indicate a persistent need for more interactive and enjoyable learning methods to stimulate these abilities. This community service program aims to socialize the storytelling method using picture media for children at the Fadilah Rahma Foundation, covering the Pekan Labuhan and Panah Hijau areas. The implementation methods used in this activity include lecture techniques through creative fairytale narration titled "CICI Ingin Terbang" (CICI Wants to Fly), dialectical question-and-answer sessions to evaluate children's understanding, and demonstration workshops where children create their own original stories and illustrations. The results of the service show an increase in enthusiasm and active involvement of participants during the learning process. Based on observations, most children were able to grasp moral messages and new vocabulary through visual aids, although some participants still required guidance in building self-confidence during presentations. This activity proves that the integration of picture media in storytelling is effective in stimulating imagination and strengthening children's verbal articulation skills. The conclusion of this service emphasizes the importance of multisensory stimulation that involves the senses of sight and hearing synchronously. The main recommendation is the need for regular story-based literacy programs to shape a generation that is wise, creative, and literate from an early age.